Unusual isothermal multimerization and amplification by the strand-displacing DNA polymerases with reverse transcription activities. Issue 1 (December 2017) - Wang, Guoping; Ding, Xiong; Hu, Jiumei; Wu, Wenshuai; Sun, Jingjing; Mu, Ying
Abstarct Existing isothermal nucleic acid amplification (INAA) relying on the strand displacement activity of DNA polymerase usually requires at least two primers. However, in this paper, we report an unusual isothermal multimerization and amplification (UIMA) which only needs one primer and is efficiently initiated by the strand-displacing DNA polymerases with reverse transcription activities. On electrophoresis, the products of UIMA present a cascade-shape band and they are confirmed to be multimeric DNAs with repeated target sequences. In contrast to current methods, UIMA is simple to product multimeric DNA, due to the independent of multiple primers and rolling circle structures. Through assaying the synthesized single-stranded DNA targets, UIMA performs high sensitivity and specificity, as well as the universality. In addition, a plausible mechanism of UIMA is proposed, involving short DNA bending, mismatch extension, and template slippage. UIMA is a good explanation for why nonspecific amplification easily happens in existing INAAs. As the simplest INAA till now, UIMA provides a new insight for deeply understanding INAA and opens a new avenue for thoroughly addressing nonspecific amplification.